Social Support Network among People Living with HIV/AIDS in Iran - Ameneh Setareh Forouzan; Zahra Jorjoran Shushtari; Homeira Sajjadi; Yahya Salimi; Masoumeh Dejman (AIDS Research and Treatment)
This study considers social network interactions as a potential source of support for individuals living with HIV/AIDS in Iran. This cross-sectional study was conducted on 224 people with HIV/AIDS who refer to behavioral counseling centers. Participants were randomly selected among all people with HIV/AIDS from these centers. Relatives were more reported as sources of support than nonrelatives. They were closer to participants, but there was difference between the closest type among relative and nonrelative supporters (P=0.01). Mean of functional support with considering the attainable range 0–384 was low (126.74  (SD=76.97)). Social support of participants has been found to be associated with CD4 cell count (P=0.000), sex (P=0.049), and network size (P=0.000) after adjusted for other variables in the final model. Totally, in this study, many of participants had the static social support network that contained large proportions of family and relatives. The findings contribute to the evidence for promotion of knowledge about social support network and social support of people living with HIV/AIDS.